Pembuatan Pakaian Dengan Memanfaatkan Serat Limbah Daun Nanas (Studi Koperasi Miwa Pineapple Di Sukaraja Kecamatan Prabumulih Timur) - Rinda Lastri, Rinda (CV. ITTC INDONESIA, 2023)
This thesis carries the title “Making Clothes Using Pineapple Leaf Waste Fiber (Study of the Miwa Pineapple Cooperative in Sukaraja, East Prabumulih District”. The aim of this thesis research is to determine the implementation of clothing making using pineapple leaf waste fiber in Sukaraja, East Prabumulih sub-district. This type of research is qualitative research. The data collection methods used in this research are observation, interviews and documentation, the author conducted interviews and directly researched clothing making activities using pineapple leaf waste fiber from 03 October to 31 October 2023. The theory used in this research is the theory of environmental sustainability is the theory by Dr.Ir.Tungkot Sipayung (1987). The research results show that the results of activities utilizing natural resources and human resources, especially the members of the miwa pineapple cooperative and the surrounding community, have the knowledge and skills to utilize the resources they have. The miwa pineapple cooperative already knows a lot about efforts to improve its cooperative, one of which is making clothes using waste fiber from pineapple leaves.